Secular changes and predictors of adult height for 86 105 male and female members of the Thai Cohort Study born between 1940 and 1990. Issue 1 (30th August 2010) - Jordan, Susan; Lim, Lynette; Seubsman, Sam-ang; Bain, Christopher; Sleigh, Adrian; ,
Abstract : Background: Height trends can be useful indicators of population health but, despite Thailand's rapid socioeconomic development since the 1950s, few studies have examined accompanying secular changes in adult height or the effects of the transition on the heights of rural versus urban populations. This study therefore sought to document average heights in different age groups of rural and urban Thais and to investigate factors associated with attained height. Methods: Data from 86 105 Thai Cohort Study participants was used to estimate mean heights for men and women in different birth year groups. Simple regression was used to calculate the change in height per decade of birth year among those based in rural or urban locations as children. Multiple linear regression was used to investigate effects of other childhood factors on height. Results: Overall, average heights were found to have increased by approximately 1 cm per decade in those born between 1940 and 1990. However, the rate of increase was 0.4–0.5 cm per decade greater among urban-based Thais compared with those from the countryside. Parental education levels, household assets, birth size, sibling number, birth rank and region of residence were also significantly associated with adult height. Conclusions: These data suggest a marked secular increase in Thai heights in the second half of the 20th century probably reflecting improved childhood health and nutrition over this time. Rural-born Thais, who benefited to a lesser extent from the changes, may face future health challenges with greater risks of, among other things, obesity and its health consequences.